Aspects of Thule Culture Adaptations in Southern Baffin Island - Sabo III, George; Jacobs, John D. (ARCTIC, 1980)
An archaeological sequence of Neo-Eskimo occupations, based upon excavations of eight Thule winter houses near Lake Harbour, Baffin Island, is outlined, beginning around A.D. 1100 and extending into the present century. Relationships between past climatic events, local environmental characteristics, and the organization of Neo-Eskimo subsistence-settlement systems are traced throughout this period of time, based on analysis of artifactual, faunal, and midden deposit data. A rescheduling of procurement systems, coupled with a shift in the emphasis of fall/winter settlement options, is seen in response to climatic/ecological changes, commencing after A.D. 1250, which affected the accessibility of bowhead whales, ringed seal, and caribou. It is suggested that flexibility in the organization of domestic units and demographic arrangements was an important cultural mechanism permitting Thule and recent Inuit populations to respond effectively to changes in their biophysical environments.